2018
DOI: 10.3389/fevo.2018.00158
|View full text |Cite
|
Sign up to set email alerts
|

Divergence in Potential Contact Pheromones and Genital Morphology Among Sympatric Song Types of the Bush Cricket Mecopoda elongata

Abstract: A well-established route to speciation in animals is via the evolution of divergent male mating signals and female preferences within a species. However, an open question is how common it is for near complete isolation to be achieved through a single signal-receiver system as opposed to multiple aspects of the mate-recognition system diverging simultaneously. The five highly divergent mate-attraction song types of the bush cricket Mecopoda elongata exemplify reproductive isolation in sympatry through long-dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Whereas speciation research has traditionally focused on single types of isolating mechanisms in a given system (e.g., genetic incompatibilities or ecological isolation; Coyne & Orr, ), recent work in invertebrates emphasizes the importance of multiple isolating mechanisms acting in concert (Dutta, Balakrishnan, & Tregenza, ; Gilman, Fowler‐Finn, & Hebets, ; Moran, Hunt, Mitchell, Ritchie, & Bailey, ). Here, we show that, contrary to prior suggestions (Sullivan et al, ), hybridization between O. arenicola and O. torridus either does not occur or is so rare that it is below the detection limits of our sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas speciation research has traditionally focused on single types of isolating mechanisms in a given system (e.g., genetic incompatibilities or ecological isolation; Coyne & Orr, ), recent work in invertebrates emphasizes the importance of multiple isolating mechanisms acting in concert (Dutta, Balakrishnan, & Tregenza, ; Gilman, Fowler‐Finn, & Hebets, ; Moran, Hunt, Mitchell, Ritchie, & Bailey, ). Here, we show that, contrary to prior suggestions (Sullivan et al, ), hybridization between O. arenicola and O. torridus either does not occur or is so rare that it is below the detection limits of our sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The role of visual cues or chemical cues in mating is unknown for the species described here and is understudied in katydids in general. Chemical cues appear to play a role in mate recognition in the Mecopoda elongata species complex in India (Dutta et al 2018), suggesting that they might also play a role in mate recognition in Neotropical species with similar acoustic or visual cues. Studies on katydid acoustic signals have revealed the presence of cryptic species that are morphologically very similar but can be distinguished by acoustic signals (Walker 1964, Walker et al 2003, Montealegre-Z et al 2011 and also cases of morphologically distinct species that have extremely similar acoustic signals (Çiplak et al 2009(Çiplak et al , Şirin et al 2014(Çiplak et al , Grzywacz et al 2017, emphasizing the importance of documenting acoustic signals for taxonomic and phylogenetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Berger and Gottsberger, 2010;Ostrowski et al, 2009;Vedenina et al, 2020). Additional signalling modalities have been identified in courtship, for example vibration in the crickets Adelosgryllus rubricephalus (Zefa et al, 2008), Cranistus colliurides (Centeno and Zefa, 2019) and Ornebius aperta (Andrade and Mason, 2000), chemical cues in the grasshoppers Chorthippus biguttulus and C. mollis (Finck and Ronacher, 2017), and probably chemical and tactile cues in the bush-cricket Mecopoda elongata (Dutta et al, 2018). In bush-crickets visual cues can be important during phonotaxis.…”
Section: Relationships Between Sound and Other Signal Modalitiesmentioning
confidence: 99%